(untitled) (Fiep Bulletin - online, 2015)
The purpose of this research was verifying the lactate profile, maximal load and flexibility of quadriceps and thigh posterior muscles after a realization of microcycle with caracteristic of strength. Ten volunteers between 17,42±0,81 years old; corporal mass 144,93±15,86 pounds, realized tests to flexibility of quadriceps and thigh posterior muscles. The volunteers realized tests of crescent load the started with 10% of maximal load (ML), increasing in 10 to 10% up to the volunteer gets exhaustion. Within a short period of time, started the training with 6 series of 4 repetitions to 90% of ML with 3 minutes in rest between the series and 5 minutes between the exercises, while 3 times per week in 6 weeks. We collected blood samples to analyze of the plasmatic lactate. The results showed a significative increase of strength (p=0,0021), resistance (p=0,00007) and flexibility of thigh posterior right muscle after the training of strength with significant p<0,05. We did not find difference in the test of crescent load by the lactate concentration rate, with a r=0,99 and p=0,0031 to correlation in the Pearson, but did not have a significative difference (p<0,05) in the value of lactate after the training sessions was lower. We verify that after the training may occur an increase of strength, resistance and not had a scathe in the flexibility.